Pengamalan Adab Guru dan Murid dalam Kitab Khulq 'Azim di Dayah Darussa'adah Cabang Faradis Kecamatan Patee Raja Kabupaten Pidie Jaya - Husaini Husaini; Syabuddin Gade (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
The background of this reseach is about the teachers and student’s behaviour understanding and implementating toward the kitab which written by Teungku Muhammad Ali Irsyad, the founder of dayah Darussaadah. The research aimed to know kinds of teachers and student’s ethical behavior in the kitab, teachers and student’s understanding toward the teachers and student’s behavior regarding to kitab Khulq ‘Aẓim, and their implementation toward the content of the kitab. Moreover, this field research conducted by using qualitative approach in descriptive method at dayah Darussaadah which affiliate to Faradis, Kecamatan Panteraja, Kabupaten Pidie Jaya. Resources of the data are kitab Khuluq 'Aẓīm, teachers and students in dayah Darussaadah. The data was collected by interview and observation. The instrumen of the data collection was interview sheet and observation sheet. Result of the research had shown that numbers of ethical behavior for teachers were 16 kinds of rules, and 24 kinds of rules for students’ ethical behavior. In conclussion, a large of number dayah member’s are understood and implementated the ethical behaviors that containing in kitab Khuluq 'Aẓīm, although many of them have any difference comprehences.